Marketing Orientation Specifics in European Union Mobile Telecommunication Market - Kurtinaitienė, Jolita (Ekonomika, 2003)
The paper presents the results of marketing orientation study in the organizational behavior perspective. It is hypothesized that marketing orientation has positive relations to performance results, innovativeness and learning orientation of the enterprises. These hypotheses are derived from the overview of the marketing orientation research and organization behavior literature.The methodology of compiling empirical research instrument is presented. The marketing orientation measurement instrument created during this study includes both innovativeness and learning orientation measurement criteria. Content validity, criterion validity and construct validity of the marketing orientation measurement instrument was assessed using statistical methods recommended by Churchill (1979). Empirical test of the marketing orientation measurement instrument in the industry of the mobile communications proved this instrument to be reliable.The interrogatory empirical research of EU mobile GSM network operators was performed during the study. Marketing orientation received the highest evaluation in Luxemburg. Finish mobile operators gave the lowest ratings for the marketing orientation criteria.The results of marketing orientation empirical research confinned positive relations between marketing orientation and enterprise performance in the mobile telecommunications industry. However hypothesis about positive relations between marketing orientation and innovativeness of the enterprise was not supported by the empirical research results of mobile GSM operators in EU countries. This phenomenon might be explained by the problems arising to mobile network operators from implementation of 3G. Hypothesis about positive relations between marketing orientation and learning orientation was strongly supported by the empirical research results in mobile telecommunications.Further implications for research are indicating a need to investigate the marketing orientation of the mobile communication operators in the candidate EU countries. In order to obtain the most objective evaluation of marketing orientation it is recommended to perform interrogatory of both the enterprise personnel and the end users of the enterprise services or products. In order to evaluate application areas of constructed marketing orientation measurement instrument it is recommended to conduct a research in other industries.